Quality of work life for health professions in Colombia's adult critical care: An integrative analysis - Laura del Pilar Quiñones-Rozo; Gladys Eugenia Canaval-Erazo (BMC, 2024)
Abstract Background Health professionals in Colombian and many parts of the world, in some cases, work in precarious conditions and intend to migrate to other countries in search of better living conditions for themselves and their families, which results in inadequate distribution worldwide and in the quality of care throughout the health system, which can ultimately influence the quality of life of patients in their health-disease processes. Purpose Describe in depth what quality of life at work is like for the health workforce in adult critical care (ACC). Methods This is an investigation of convergent parallel mixed methods approach that are integrated by means of a matrix in terms of convergence, divergence, and complementarity. Two methods are used: a transversal analytical method in which three instruments were applied to 209 participants to study the relationship between Quality of Life at Work, exposure to psychosocial risks, compassion fatigue and the intention to rotate; other than from the experiences narrated by 10 Human Talent in Health explore organizational practices in critical care. Results The dimension of quality of work life with the greatest dissatisfied was the management of free time (77%), the most compromised psychosocial risk was the pace of work (84%). They have high compassion satisfaction (67%) and there is an intention to migrate to another country (66%). The narrative results in discrimination/harassment as normalized practices and faceless spirituality. The integration of mixed methods shows convergence between the use of the instrument that measures quality of life at work and the narratives of the participants, complementarity with the other instruments, and divergence regarding the intention to rotate to another health institution. Conclusion The positive trend that converges with the two approaches is that of safety at work and well-being achieved through work, embodied in the constant updating of technology and care protocols, experience time, balance between salary and work effort, staffing and supplies, and disconnection with work.